Pandemic is a matter of space - Hammad, Manar (E|C, 2021)
Space semiotics have been originally deviced in order to account for the meaning perceived by people moving in a void organized by architectural items. Covid19 pandemic posits another kind of problem, where human beings are passive, while the active agent is a virus moving from human body to human body. The virus should be examined as the syntactic subject, for whom human bodies appear as places whose access is defended by efficient barriers (skin) while entrance openings (nose, mouth, eyes) have conditional attributes. The virus gets out from bodies after duplication. This duplication posits a semantic problem for the identification of a collective actor acting as subject.